Bilateral total hip arthroplasty in ankylosing spondylitis: a systematic review. Issue 7 (July 2019) - Lin, David; Charalambous, Alexander; Hanna, Sammy A.
Abstract : Ankylosing Spondylitis (AS) can commonly involve the hip joint and cause significant mobility problems. Total hip arthroplasty (THA) on a single side alone will not restore mobility in patients with bilateral disease. We performed a systematic review of the available literature to determine the changes in objective outcome measures and complications of bilateral THA in patients with advanced AS. Four studies, a total of 114 THAs, were included in the study. The average patient age was 32.9 years and the average follow-up time was 59.5 months. All studies reported a significant improvement in hip function, patient satisfaction and patient mobility following bilateral THA. Harris Hip Score (HHS) improved by a mean of 60.6 points post-operatively. Complications included five intra-operative fractures (4.4%) and three transient nerve palsies (2.6%). There were two dislocations (1.8%) that were successfully managed with closed reduction. Seven hips required revision, with the most common cause being aseptic loosening. Twelve hips (10.5%) developed heterotopic ossification consistent with Brooker Class 1 or 2 with no reports of re-ankylosis. This review suggests that bilateral THA is a safe and effective treatment of advanced hip disease in AS. Attention must be paid to the highly demanding technical aspects of this procedure to reduce the risk of significant complications. Debate still exists on the ideal prosthesis, fixation method and approach to use but this review presents data from several series of uncemented prostheses that have good post-operative results. Cite this article: EFORT Open Rev 2019;4:476-481. DOI: 10.1302/2058-5241.4.180047